The Impact Of Internal Marketing On The Implementation Of Strategic Orientations And Product Innovation In Manufacturing Industry - CHAN, SEOW HONG (2005)
Recent studies have demonstrated the effects of internal marketing on market orientation and strategic orientations on organizational innovation performance. However, to the best of our knowledge no attempt has yet to be made to empirically test internal marketing framework that formally interrelates internal marketing, strategic orientations and product innovation.